2021
DOI: 10.3390/insects12080693
|View full text |Cite
|
Sign up to set email alerts
|

Mating-Induced Trade-Offs upon Egg Production versus Fertilization and Offspring’s Survival in a Sawfly with Facultative Parthenogenesis

Abstract: Investigation of mating-induced trade-offs between reproduction and survival is conducive to provide evolutionary insights into reproductive strategies and aging. Here, we used RNAseq and bioinformatics to reveal mating-induced changes of genes and pathways related to reproduction and survival in female Cephalcia chuxiongica, a pine defoliator with facultative parthenogenesis and long larval dormancy. Results showed that mating induced substantial downregulation on genes and pathways associated to immunity, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Previous studies generally found that mating induces the upregulation of egg production and fertilization rate [ 32 , 35 , 36 , 41 ], whereas in C. chuxiongica, mating induced divergent reproductive response, with downregulation on genes related to egg production, while upregulation on genes related to egg fertilization [ 38 ]. In the present study, functional enrichment analysis in S. frugiperda females showed there is more reproduction related terms/pathways enriched to upregulated DEGs than to downregulated DEGs (10:1) at 0 h postmating, which is less (1:14) at 6 h postmating, and then more (16:0) again at 24 h postmating.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies generally found that mating induces the upregulation of egg production and fertilization rate [ 32 , 35 , 36 , 41 ], whereas in C. chuxiongica, mating induced divergent reproductive response, with downregulation on genes related to egg production, while upregulation on genes related to egg fertilization [ 38 ]. In the present study, functional enrichment analysis in S. frugiperda females showed there is more reproduction related terms/pathways enriched to upregulated DEGs than to downregulated DEGs (10:1) at 0 h postmating, which is less (1:14) at 6 h postmating, and then more (16:0) again at 24 h postmating.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that mating may also promote trade-offs between reproduction and survival, with increased reproductive activities after mating being likely to incur cost on soma maintenance [ 36 , 37 , 38 , 41 ]. In the present study, however, mating induced upregulation on response (such as response to external biotic stimulus, response to bacterium and response to external stimulus; Tables S8–S11 ) and soma maintenance (such as immune activity, stress reaction and detoxification; Tables S8–S11 ) related processes in S. frugiperda females at 0, 6 and 24 h postmating ( Figure 5 a–c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations have been made in female Cephalcia chuxiongica, where reproductive-related genes are upregulated from 1 to 24 h after mating, while immune genes remain downregulated. After 24 h post-mating, longevity-related genes start to decline [102]. It is worth mentioning that the expression of female immune genes after mating shows species-specific, and even interspecies-specific, differences [103].…”
Section: Regulation Of Gene Expression In Insect Post-mating Responsesmentioning
confidence: 99%